Cutaneous ALCL mimicking malignant epithelial tumor in the head and neck region - Abdullah, Kahairi; Yusuf, Suhaimi; Ramachandran, Kalavathy (2011)
Objective: To highlight a rare case of cutaneous ALCL in the head and neck region. Method used: Case report. Result: The patient presented with large ulcerative lesion in the lateral neck region and at presentation has already had multiple lung metastasis. With its aggressive behavior and appearance, this lesion is mimicking malignant epithelial tumor of the lateral neck. Conclusion: This case has highlighted that cutaneous ALCL may occur in the head and neck region and behave aggressively. It may present in an unusual way, and this may cause delay in the diagnosis. Therefore, early diagnosis is essential so that treatment can be instituted early for a better prognosis.